Arbitration as an Alternative to Dispute Resolution in the Indonesian Legal System Analysis of Legal Effectiveness and Certainty - Sabilah Widyanti; Desti Nur Fitriah Pasaribu; Farida Maharani Nasution; Annisa Divanny Nasution; Misli Ihsana Darlian (Jurnal Cendikia ISNU SU, 2024)
The increase in the complexity of business relationships requires a dispute resolution mechanism that is able to provide legal certainty quickly, efficiently, and fairly. Dispute resolution through litigation often faces obstacles in the form of lengthy procedures, high costs, and the potential to disrupt the business relationship of the parties. In this context, arbitration is present as an alternative form of dispute resolution that has gained recognition in the Indonesian legal system through Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This study aims to analyze the position of arbitration as an alternative solution to dispute resolution, its implementation mechanism, and the legal force of arbitration awards in ensuring legal certainty for the parties. The research uses a normative juridical method with a legislative approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed qualitatively descriptively through deductive reasoning. The results of the study show that arbitration has advantages in the form of flexible procedures, faster dispute resolution, relatively efficient costs, confidentiality of the examination process, and freedom of the parties in choosing arbitrators who have competence in the field of dispute. In addition, final and binding arbitration awards provide legal certainty while ensuring the effectiveness of dispute resolution, although its implementation still faces challenges in the form of low utilization of arbitration and obstacles to the execution of awards in practice. Therefore, arbitration is an effective dispute resolution instrument to support a conducive business climate, increase legal certainty, and realize fast, efficient, and fair dispute resolution.